ANALISIS KINERJA AGROINDUSTRI KELAPA SAWIT PT ABC DI KABUPATEN MESUJI MENGGUNAKAN METODE BALANCED SCORECARD - Ervina Dwicahyani; Muhammad Irfan Affandi; Maya Riantini (Lampung University, 2019)
This study aims to determine the performance of PT ABC based on the Balanced Scorecard in Mesuji Regency. The research is a case study, conducted by using secondary data of PT ABC from 2015-2017 periods to analyze financial perspectives. For other perspectives were conducted through the calculation of the results of interview using a questionnaire. The population in this study are PT ABC customers and employees. While the samples are five companies for customer respondents, and 60 people for employee respondents. Data collection research was conducted in January 2019. The result of the research showed that the overall performance of PT ABC was in fairly good category. In a financial perspective, variables of return on investment and total assets turnover have shown good performance. For the customer perspective, it showed good performance by looking at variables of customer satisfaction and customer retention. In the perspective of internal business processes, it showed that conditions were still worse as the operating profit margin has decreased and the index